Creation of a plasma collection for the search of diagnostic biomarkers of glial tumors - E. P. Omelchuk; N. N. Timoshkina; D. Yu. Gvaldin; N. A. Petrusenko; E. E. Rostorguev; I. A. Novikova; O. I. Kit (Кардиоваскулярная терапия и профилактика)
Aim. To create a collection of plasma samples of patients with brain tumors (BTs) for the development of a diagnostic microRNA (ribonucleic acid) panel of glial tumors.Material and methods. Plasma samples of patients with benign and malignant BTs were obtained by double centrifugation of whole blood and then frozen at -75оС.Fifty-nine RNA samples isolated from blood plasma were analyzed by next-generation sequencing (NGS).Results. Currently, the biobank contains samples from 339 patients with primary and secondary BTs and 10 control group individuals (698 samples — 2 plasma aliquots per individual), including 143 men and 206 women. The age of the patients ranged from 19 to 91 years (median — 56 years). Primary BTs (41%) included two following groups: benign (33,7%) and malignant (66,3%). Meningiomas constituted the bulk (91%) of the benign BTs. Among the malignant tumors, glioblastomas (46,7%) and astrocytomas (41,6%) prevailed, while oligodendrogliomas and ependymomas accounted for only 9,1 and 2,5%, respectively. Secondary BTs (59%) are represented by recurrent glial tumors (92,5%) and metastatic tumors (7,5%) of lung cancer (71,4%) and breast cancer (28.6%). A protocol for the primary preparation of liquid biopsy samples was implemented, which made it possible to obtain high-quality deoxyribonucleic acid libraries for the selected microRNA profiling platform.Conclusion. The creation of a plasma sample collection is the basis for searching circulating biomarkers of BTs.